Production of Al-Ti-C Grain Refiners with the Addition of Elemental Carbon and K2TiF6 - Toptan, Fatih; Kerti, Isil; Daglilar, Sibel; Sagin, Ahmet; Karadeniz, Omer F.; Ambarkutuk, Aysin (JOHN WILEY & SONS, 2011)
Al-Ti-B grain refiners are widely used as aluminum grain refiners. Despite the problems in application, Al-Ti-C refiners have an increasing demand in recent years. In the present work, Al-Ti-C grain refiners with different Ti:C ratios were produced by in-situ method with the addition of elemental carbon into the Al-Ti master alloy (master alloy method) and the addition of K2TiF6 and elemental carbon powder mixture into the commercially pure aluminum (flux method). The effects of production method and Ti: C ratio on the grain refinement process were investigated using Alcoa Cold finger Test and so optimum conditions were determined. The best performance was accomplished with the refiner produced at 1300 degrees C with the master alloy method.
Keywords: Aluminum; Al-Ti-C Grain Refiners; Elemental Carbon; K2TiF6; ALTIC MASTER ALLOYS; REFINING EFFICIENCY; PERFORMANCE; Metallurgy & Metallurgical Engineering